REFORMASI LAYANAN PUBLIK : ANTARA HARAPAN DAN REALITA - Eko Setiyo Utomo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
The government is an agent which provides public services should improve the quality of the services. It should be recognized that delivering public service is not yet on the good level. The people need the services at the high level. Public service improvement must go to improving public service itself. That is hoped that the meaning and involving of the public service would come to development Indonesian people totally. Finance Public Management Reform is one of the efforts of the government to answer public requirement.